Faktor yang Mempengaruhi Profitabilitas pada Perusahaan Consumer Non Cyclical Tahun 2021-2023 - Nurul Laily Barsyah; Hermi Hermi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Companies run businesses with the aim of gaining profits that can be measured by profitability. Profitability is a measure that evaluates a company's ability to generate profits or profits over time. This study aims to analyze the effect of accounts receivable turnover, sales growth, inventory turnover, and cash turnover on profitability. This research was conducted on non-cyclical consumer companies listed on the Indonesia Stock Exchange. This research is a descriptive quantitative study. This study uses panel data consisting of cross-section data, namely non-cyclical consumer companies with a time series for the period 2021-2023. The sample used in this study was 59 companies. The analysis technique used in this study is panel data regression. The results of the analysis show that (1) Accounts receivable turnover has a positive and significant effect on profitability in the non-cyclical consumer sector. (2) Sales growth does not affect profitability in the non-cyclical consumer sector. (3) Inventory turnover has a positive and significant effect on profitability in the non-cyclical consumer sector. (4) Cash turnover does not affect profitability in the non-cyclical consumer sector.